PACHA MAMA AND SUMAK KAWSAY: THE CONSECRATION OF AN ENVIRONMENTAL CONSTITUCIONALISM - Miranda Alves, Jaime Leonidas (Unoesc International Legal Seminar, 2017)
Law is the field of knowledge that has the goal to regulate the life in community. More than that, it is a phenomenon; a social fact. In that sense, the gradual development of society drives the legal science to also develop, restructuring its concepts and employing a rereading in its institutes. Indeed, it is known that law sometimes, by the use of dialectical method, rebuilds itself, given the need to oppose some dogmas to epistemological assumptions. It is in this vein, that constitutional theories are brought to life, making contrast to different moments in the history of law, as well as cultural development of social groups, innovating greatly the interpretation given to several classic legal institutions. This paper seeks, through the systemic analysis of the new Constitutions of Bolivia and Ecuador, to question whether if it is possible to think in a new epistemology regarding the protection of nature’s rights, as a consequence of the recognition of indigenous worldviews. So first it was determined the existence of a new Latin American constitutionalism to then engendering in realizing the consequences of this hermeneutic break to fundamental rights especially with regard the nature law in its objective and also subjective perspective. This research was developed under the scrutiny of constitutional hermeneutics and dialectics technique.